Navigating Illusions: Unraveling Confirmation Bias using Cognitive Dissonance in Virtual Influencers on Social Media Platforms - Busye Uysal; Ronny Estrella (International Telecommunications Society (ITS), 2024)
While policymakers are beginning to address AI-generated content on social media, there remains a notable gap in regulatory approaches towards Virtual Influencers. The capability of Virtual Influencers to autonomously upload content presents significant challenges, especially in distinguishing between human and AI-generated content, which in turn affects user trust. To tackle this issue, this study proposes the implementation of disclosure flags specifically for content created by Virtual Influencers. This research involved a questionnaire administered to 189 Instagram users to explore how disclosure flags influence their perceptions and acceptance of Virtual Influencer's content. The findings reveal that although disclosure flags increase awareness, they do little to foster critical engagement with the content. The study emphasizes the importance of professional oversight and user-driven content moderation through disclosure flags to maintain the integrity of digital content. These insights are crucial for policymakers and platform designers working towards a transparent digital environment. The evident lack of transparency around Virtual Influencers highlights the urgent need for clearer regulatory frameworks. Therefore, this research advocates for comprehensive strategies that integrate these flags with broader educational and regulatory measures to enhance digital literacy and critical engagement among users.
Keywords: 330; Virtual Influencers; Social Robots; Social Media; Cognitive Dissonance; Affective Behavior; Disclosing Flags